A Report of Rosai-Dorfman Disease in an Adolescent - Emmanuella Amoako; Kwadwo Apeadu Danso; Rosemary Sefakor Akuaku; Kofi Ulzen-Appiah (Hindawi Limited, 2022)
Rosai-Dorfman disease (RDD) is a rare disease of unknown cause. It is a benign self-limiting condition characterized by the accumulation of activated histiocytes in the sinusoids of lymph nodes and/or extranodal tissues. Massive cervical lymphadenopathy as the initial manifestation tends to raise the initial odds in favour of a lymphoma, and thus reducing the threshold to performing a simple biopsy cannot be overestimated. Herein, we report a 13-year-old adolescent who presented with a progressive posterior left-sided neck swelling. Our diagnosis of RDD was established by demonstrating emperipolesis in histology and S100 positivity in immunohistochemistry as stated in the literature. Although the condition is known to be self-limiting, evidence from the literature and our case management shows that medical therapy can hasten remission in pediatric cases.